1994
DOI: 10.1111/j.1432-1033.1994.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher Plant Light‐Harvesting Complexes LHCIIa and LHCIIc are Bound by Dicyclohexylcarbodiimide During Inhibition of Energy Dissipation

Abstract: We have investigated the binding to proteins of the photosynthetic apparatus of the carboxymodifying agent dicyclohexylcarbodiimide, (cHxN),C ; this inhibits the protective dissipation of excess absorbed light energy (qE) by the light-harvesting apparatus of photosystem I1 (LHCII), suggesting that carboxyl amino-acid side chains within hydrophobic protein domains may be involved in qE. (cHxN),I4C was used to label thylakoids and photosystem I1 particles, so as to identify proteins which may be involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
92
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 47 publications
(55 reference statements)
2
92
0
2
Order By: Relevance
“…CP29 antisense plants showed only marginal changes in the PSII antenna other than the loss of CP29 and a fraction of CP24. The loss of CP26 or CP29 had no effect on the acclimation of the PSII antenna to light quantity; for all lines, growth light-dependent changes in LHCII content were equivalent to between 1 and 1.5 extra trimers per PSII in LL-grown plants, consistent with previous observations for Arabidopsis and other species (Mäenpää and Andersson, 1989;Walters et al, 1994;.…”
Section: Altered Psii Function In Antisense Linessupporting
confidence: 79%
“…CP29 antisense plants showed only marginal changes in the PSII antenna other than the loss of CP29 and a fraction of CP24. The loss of CP26 or CP29 had no effect on the acclimation of the PSII antenna to light quantity; for all lines, growth light-dependent changes in LHCII content were equivalent to between 1 and 1.5 extra trimers per PSII in LL-grown plants, consistent with previous observations for Arabidopsis and other species (Mäenpää and Andersson, 1989;Walters et al, 1994;.…”
Section: Altered Psii Function In Antisense Linessupporting
confidence: 79%
“…Demmig-Adams and Adams, 1996;Gilmore et al, 1996b), and some have suggested that the minor LHCII components play a major role in qE in vivo Bassi et al, 1993;Crofts and Yerkes, 1994;Walters et al, 1994;Gilmore et al, 1996b;Pesaresi et al, 1997). The doubt about the involvement of LHCIIb is based partly on the study of mutants and/or developing chloro- plasts, which lack LHCIIb but still show qE (Härtel and Lokstein, 1995;Jahns and Schweig, 1995;Gilmore et al, 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…Various reports suggest that qE occurs in LHCII Horton et al, 1996), where the xanthophyll cycle carotenoids are bound (Peter and Thornber, 1991; Bassi et al, 1993;Ruban et al, 1994b) and where proton-active sites involved in qE have been identified Pesaresi et al, 1997). It has been suggested that CP26 and CP29, two of the minor components of LHCII, have a major role in qE Bassi et al, 1993; Crofts and Yerkes, 1994;Walters et al, 1994;Pesaresi et al, 1997;Gilmore et al, 1996b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The successful reconstitution of the minor Chl a and b antenna complexes, CP29, CP26, and CP24 using maize Lhcb4, -5, and -6 apoproteins overexpressed in Escherichia coli, was recently reported (14)(15)(16). The recombinant proteins exhibit absorption, fluorescence emission, and CD signals which closely match those of the native complex while even peculiar biochemical features such as DCCD binding (17) were reproduced (18). The recombinant CP29 system can therefore be used for the experimental analysis of the relevant parameters that have been left unknown after the structural work on LHCII by Kuhlbrandt and co-workers.…”
mentioning
confidence: 99%